2019
DOI: 10.1002/adfm.201902521
|View full text |Cite
|
Sign up to set email alerts
|

Porous Enzymatic Membrane for Nanotextured Glucose Sweat Sensors with High Stability toward Reliable Noninvasive Health Monitoring

Abstract: Development of reliable glucose sensors for noninvasive monitoring without interruption or limiting users' mobility is highly desirable, especially for diabetes diagnostics, which requires routine/long-term monitoring. However, their applications are largely limited by the relatively poor stability. Herein, a porous membrane is synthesized for effective enzyme immobilization and it is robustly anchored to the modified nanotextured electrode solid contacts, so as to realize glucose sensors with significantly en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
101
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 143 publications
(101 citation statements)
references
References 34 publications
0
101
0
Order By: Relevance
“…Another fundamental limitation of PB‐based sensors is its operational stability. A number of studies have reported and characterized the degradation of the PB layer in aqueous solutions, especially in alkaline environments . Efforts have been made to improve the stability of PB structure, but the fabrication methods are typically complicated and time‐consuming .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another fundamental limitation of PB‐based sensors is its operational stability. A number of studies have reported and characterized the degradation of the PB layer in aqueous solutions, especially in alkaline environments . Efforts have been made to improve the stability of PB structure, but the fabrication methods are typically complicated and time‐consuming .…”
Section: Resultsmentioning
confidence: 99%
“…A number of studies have reported and characterized the degradation of the PB layer in aqueous solutions, especially in alkaline environments . Efforts have been made to improve the stability of PB structure, but the fabrication methods are typically complicated and time‐consuming . The reason for the instability of the PB structure is likely due to the strong interaction between Fe III ions and hydroxyl ions (OH − ), which can be attributed to inherent buffer conditions (especially, when operating at a pH higher than 6.4) and the H 2 O 2 reduction .…”
Section: Resultsmentioning
confidence: 99%
“…However, the electrochemical sensors or immunosensors normally consist of three major parts—substrate, amplifying matrix, and detecting biomolecules. Based on applications, various kinds of substrate, e.g., flexible, wearable, polymide film, Ti/Au 11,12. and paper‐based substrates, are used for detecting different kinds of cancer biomarkers.…”
Section: Introductionmentioning
confidence: 99%
“…The gold nano-dendrites increase the surface area of the electrode to improve the sensitivity and stability of the sensor. 13,30 Figure 2b shows the oxidation peak from cyclic voltammetry (CV) of the functionalized electrode in phosphate-buffered saline (PBS) solution, with the subsequent addition of nicotine (0 -30 μM). The oxidation peak increases in its height with increasing concentration of nicotine and is centered at 0.8 V, the potential chosen for amperometric testing.…”
Section: Abstract: Nicotine Monitoring Electrochemical Devices Wearmentioning
confidence: 99%